EFFECTS OF DICHLOROMETHANE FRACTION OF ETHANOL EXTRACT OF PHYLLANTHUS AMARUS LEAF ON 1, 2-DIMETHYLHYDRAZINE INDUCED HEPATO-RENAL DYSFUNCTION IN SWISS ALBINO MICE - Omoregie, Frank O.; Uboh, E. Friday (FUDMA Journal of Sciences, 2024)
The objective of this study was to assess the impact of the Dichloromethane (DCM) fraction of the ethanol extract from Phyllanthus amarus leaves on hepato-renal toxicity induced by 1,2-dimethylhydrazine (DMH) in Swiss albino mice. A total of twenty-five male Swiss albino mice, each weighing between 21-25g, were used in a 90-day (12-week) experiment. The mice were divided into five groups: Group 1 (Control), Group 2 (25 mg/kg DMH + 250 mg/kg DCM fraction of P. amarus), Group 3 (25 mg/kg DMH + 350 mg/kg DCM fraction of P. amarus), Group 4 (25 mg/kg DMH + 450 mg/kg DCM fraction of P. amarus), and Group 5 (25 mg/kg DMH). Each cage, made of mental steel, housed five animals. The mice had free access to food and clean water and were kept under a 12-hour light/dark cycle. DMH was administered orally at a dose of 25 mg/kg body weight using a dolphin gavage, three times a week for a duration of eight weeks. Following the end of DMH treatment, the DCM fraction of the ethanol extract of P. amarus leaves was administered orally for an additional four weeks. The animals were fasted overnight and were sacrificed after being anesthetized using urethane. Blood was collected into plain and EDTA containers for biochemical investigation. Liver and kidneys were excised and homogenized for the assay of some antioxidant biomarkers. Liver function indices were assayed as well as kidney function biomarkers.  Portions of the liver and kidney were used for histological analysis Results obtained showed that...
Keywords: Phyllanthus amarus; 1, 2 –dimethylhydrazine (DMH); Dichloromethane (DCM); Antioxidants; Liver; Kidney; Function biomarkers